2017
DOI: 10.4172/2165-7939.1000383
|View full text |Cite
|
Sign up to set email alerts
|

An Adult Cervical Intramedullary Arachnoid Cyst: Case Report and Review

Abstract: Spinal arachnoid cysts are uncommon benign lesions that occur in the spinal axis, and can cause spinal cord or nerve roots compression and may become clinically relevant.The authors report a 49-year-old woman who presented progressive onset of cervical pain with distal paraesthesia of the upper limbs associated to an intramedullary arachnoid cyst in the mid-cervical spine diagnosed by MRI.From the literature review, only six cases in patients over 18-year-old were found, all with thoracic location and one with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The trigger point for deterioration and cyst behavior is still unclear, 15 but if the patient is asymptomatic, a wait and periodic scan approach could be tried. 25 The timing of surgery following deterioration in symptoms and examination is this article review is showing better outcome with early intervention after deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…The trigger point for deterioration and cyst behavior is still unclear, 15 but if the patient is asymptomatic, a wait and periodic scan approach could be tried. 25 The timing of surgery following deterioration in symptoms and examination is this article review is showing better outcome with early intervention after deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of IMAC are few and to date, only 24 cases have been reported. [ 1 - 3 , 5 - 7 , 9 - 14 , 16 - 21 , 23 - 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…Although most reports emphasize surgery for symptomatic cases, Fonseca and Ratilal demonstrated that clinical observation can be done in mild or asymptomatic cases. [ 7 ] The late presentation of symptoms in some adult cases can be used as a reference in support of observation of mild or asymptomatic patients. However, the literature is limited and we can only speculate about the natural history of IMAC at this point.…”
Section: Discussionmentioning
confidence: 99%
“…Fenestration of the cyst with or without shunting to the subarachnoid space is another available treatment modality. Although surgery is the preferred approach in fact available one, a recent case reported by Fonseca and Ratilal [19] advocate "wait and scan" approach as a good therapeutic choice if patient is asymptomatic or mildly symptomatic.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Fonseca and Ratilal 2017 [19] 49 years/female Progressive cervical pain with episodic B/L distal paresthesia these lesions should undergo for surgical treatment as they afford very good clinical results, excellent prognosis and almost no recurrence. It's time to provide focused attention on their occurrences in asymptomatic patient.…”
Section: D9-d12mentioning
confidence: 99%